Asesmen dalam Pendidikan : Memahami Konsep,Fungsi dan Penerapannya - Natasya Lady Munaroh (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research comprehensively discusses assessment in education, starting from the meaning, function, principles, types of assessment, to the assessment techniques used. Assessment is defined as the process of gathering information to make decisions regarding students, curriculum, programs, and educational policies. The assessment function includes understanding student learning progress, improving teaching strategies, and determining graduation. The assessment principles include keeping track, checking up, finding out, and summing up, and focus on competency achievement, validity and reliability of assessment tools, balance of process and results, use of various methods and tools, continuous assessment, and assessment functions. Types of assessment include diagnostic, formative, summative, selective, and placement assessments, as well as assessment of learning, assessment for learning, and assessment as learning. Assessment techniques are divided into test and non-test techniques. Test techniques include performance assessment, product assessment, project assessment, and portfolio assessment. Non-test techniques include observation sheets. This paper is expected to provide a better understanding of assessment and its application in improving the quality of education.